Adaptations and mechanisms of human heat acclimation: Applications for competitive athletes and sports - Periard, J. D.; Racinais, S.; Sawka, M. N. (Scandinavian Journal of Medicine & Science in Sports, 2015)
Exercise heat acclimation induces physiological adaptations that improve thermoregulation, attenuate physiological strain, reduce the risk of serious heat illness, and improve aerobic performance in warm-hot environments and potentially in temperate environments. The adaptations include improved sweating, improved skin blood flow, lowered body temperatures, reduced cardiovascular strain, improved fluid balance, altered metabolism, and enhanced cellular protection. The magnitudes of adaptations are determined by the intensity, duration, frequency, and number of heat exposures, as well as the environmental conditions (i.e., dry or humid heat). Evidence is emerging that controlled hyperthermia regimens where a target core temperature is maintained, enable more rapid and complete adaptations relative to the traditional constant work rate exercise heat acclimation regimens. Furthermore, inducing heat acclimation outdoors in a natural field setting may provide more specific adaptations based on direct exposure to the exact environmental and exercise conditions to be encountered during competition. This review initially examines the physiological adaptations associated with heat acclimation induction regimens, and subsequently emphasizes their application to competitive athletes and sports.